Implikasi Yuridis Keputusan Mahkamah Konstitusi No. 69/PUUXIII/2015 Tentang Perjanjian Perkawinan Terhadap Harta Bersama Bagi Pernikahan Campuran - Badrut Tamam (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2021)
ABSTRACT Mixed marriages that occur in Indonesia, the perpetrators often do not pay attention to and know the steps of the rules before making a mixed marriage, especially those concerning the joint assets acquired throughout the marriage. someone who does mixed marriages cannot freely buy land rights in Indonesia because his spouse is a foreign national. This is due to the limitation of land ownership rights stipulated in Indonesian land law article 1 jo Article 21 of Law Number 5 Year 1960 which is based on nationality, in fact it has a socialization that is by conducting an Agreement on marriage, but lack of knowledge of mixed marriages so that it is still many do not enter into marriage agreements. In October 2016 the Constitutional Court gave decision No. 69 / PUU / XIII / 2015 made a shift in the meaning and norms related to the marriage agreement which impacted the joint assets for this study entitled